Access to a Key Building Block for the Prostaglandin Family via Stereocontrolled Organocatalytic Baeyer–Villiger Oxidation. Issue 29 (7th May 2019) - Zhu, Kejie; Hu, Sha; Liu, Minjie; Peng, Haihui; Chen, Fen‐Er
Abstract: A new protocol for the construction of a crucial bicyclic lactone of prostaglandins using a stereocontrolled organocatalytic Baeyer–Villiger (B‐V) oxidation was developed. The key B‐V oxidation of a racemic cyclobutanone derivative with aqueous hydrogen peroxide has enabled an early‐stage construction of a bicyclic lactone skeleton in high enantiomeric excess (up to 95 %). The generated bicyclic lactone is fully primed with two desired stereocenters and enabled the synthesis of the entire family of prostaglandins according to Corey′s route. Furthermore, the reactivity and enantioselectivity of B‐V oxidation of racemic bicyclic cyclobutanones were evaluated and 90–99 % ee was obtained, representing one of the most efficient routes to chiral lactones. This study further facilitates the synthesis of prostaglandins and chiral lactone‐containing natural products to promote drug discovery. Abstract : The core of the matter : A crucial bicyclic lactone containing two stereocenters was accessed through a new stereocontrolled organocatalytic Baeyer–Villiger oxidation of racemic cyclobutanone with aqueous hydrogen peroxide. This key intermediate enabled the assembly of the prostaglandin family of natural products.